"Why am I to blame when the law is on my side?" A study of crises, public opinion and frames. Issue 4 (9th November 2015) - Holmgreen, Lise-Lotte
Abstract : Purpose: – The purpose of this paper is to discuss why social media frames may exert substantial influence on the image of organisations and even trigger organisational crises. Design/methodology/approach: – The study applies the theoretical approaches of crisis, framing and stakeholder theory to examine social media constructions of organisational behaviour. A recent case from the Danish restaurant industry exemplifies the structuring of social media frames and their impact on organisational image. Findings: – The results of the study confirm the findings of previous studies but with the crucial addition that the power of social media frames is closely connected to their drawing on basic cultural and social beliefs that unite stakeholders across potentially different interests and identities. Research limitations/implications: – The study is qualitative and applies a small dataset. To confirm the findings, further studies need to be conducted. Social implications: – This paper sheds light on an issue which continues to be highly relevant for organisations. By gaining insight into the conceptual nature of frames and stakeholder motivations, which guide social-media entries, they may be better equipped for meeting the demands of the public and thus for preventing crises. Originality/value: – This is a field of research that continues to develop concurrently with the development and spread of social media. By analysing in detail how frames are constructed, the study contributes to research in the field.